Management of Overseas Refugees in North Sumatra in the Perspective of Human Security - Khairiah, Nalil; Rahmi, Atikah; Martinelli, Ida (Budapest International Research and Critics University, 2021)
The objective of this study was to determine the management of the handling of refugees in North Sumatra in the perspective of Human Security. Handling refugees internationally is regulated in international refugee conventions, The 1951 convention Relating the Status of Refugees, The 1967 Protocol Relating to the Status of Refugees, the Convention Relating to the Status of Stateless Person (1954), and Convention Governing the specific Aspects of Refugees Problems In Africa (1969). These conventions are a form of protection for refugees. However, the problem is that Indonesia has not ratified the 1951 convention and the 1967 protocol on refugees, so that Indonesia cannot directly determine the status of the foreign arrivals, but the UN agency UNHCR. Meanwhile, Indonesia, especially North Sumatra, is a transit point for foreign refugees to save themselves. Humanely, the Indonesian government cannot refuse or forcibly repatriate the refugees. Therefore, based on the Regulation of the Republic of Indonesia No. 125 of 2016 concerning the Handling of Overseas Refugees, policies have been formulated in handling refugees which include finding, sheltering, securing and monitoring immigration so that the management of the handling of refugees reflects a positive dimension of human security, namely paying attention to the safety of individual refugees. and at the same time provide protection to Indonesian citizens. The research method used is descriptive qualitative. The results of the study indicate that the management of the handling of refugees in North Sumatra has been carried out in a coordinated manner according to existing regulations.